Long-Term Course of Shoulders After Ultrasound Therapy for Calcific Tendinitis: Results of the 10-Year Follow-Up of a Randomized Controlled Trial. (September 2018) - Pieber, Karin; Grim-Stieger, Martina; Kainberger, Franz; Funovics, Martin; Resch, Karl-Ludwig; Bochdansky, Thomas; Pablik, Eleonore; Ebenbichler, Gerold
Abstract : Objective: The aim of the study was to follow both the structure- and function-related long-term course of shoulders that had been treated with therapeutic ultrasound for symptomatic calcific tendinitis. Design: This is a long-term follow-up of 45 shoulders (37 patients) that had been treated for symptomatic calcific tendinitis with either a series of ultrasound or sham ultrasound 10 yrs ago. The main outcome variables were presence of calcium deposits and subacromial impingement on standardized x-ray imaging, shoulder symptoms (Binder score), and function (Constant score). Results: At 10 yrs, a similar proportion of calcium deposits had resolved in 78% of the originally ultrasound treated compared with 83% of sham-treated shoulders, whereas at 9 mos, significantly more calcium deposits had been resolved in the ultrasound group ( P = 0.045). Relative to baseline, shoulder symptoms and function had significantly improved at both the 10-yr and 9-mo follow-up examinations with no significant differences between groups. Regular sports performance at baseline predicted a favorable long-term outcome. Conclusions: Symptomatic calcific tendinitis of the shoulder has a good likelihood to completely resolve in the long term. Treating the calcium deposit effectively, however, may not be causal to the recovery from symptoms and function in calcific tendinitis. Abstract : Supplemental digital content is available in the text.